Knowledge organization in the dynamics of research in the scientific literature of articles at Brapci - Freitas, Juliana Lazzarotto [UNESP]; Nascimento, Bruna Silva do; Bufrem, Leilah Santiago [UNESP] (Pontificia Universidade Catolica Campinas, 2014)
The aim of this paper is to analyze the research dimensions expressed in the literature in the field of knowledge organization. We consider that scientific investigation developed in certain social contexts and historical conjunctures reflects the changes and contradictions present in these contexts, both in its organization and applications. This process is illustrated from a corpus of 105 articles retrieved from the referential database of journal articles on Information Science between 2003 and 2012. Endnote and Excel software were used for organizing and analyzing the data collected. The articles are categorized according to their object and methodological approach, as well as their theoretical foundations through the study of citations. Throughout this investigation, we point out the most expressive and active authors in the field of knowledge organization in Brazil. We also identify the journals that are more devoted to the theme and we conclude that Brazilian scientific production on the theme is irregularly distributed over the period of time analyzed, peaking in 2011 when 18,27% of the total number of articles were published. We conclude by establishing the relationship between theoretical currents of knowledge organization and the prevalent approaches and themes found in the corpus. The focus of the most prevalent research approaches were the theoretical and linguistic approaches and the type of analysis was documentary.
Keywords: Scientific journal literature; Knowledge organization; Scientific research